(untitled) (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
The main objective of this research is to investigates the practice of farmer managed irrigation system and existing conflicts management practice of farmer managed irrigation system (FMIS), which concerning the construction, operation, maintenance and conflict management of local irrigation systems. The farmers of the study area managed the irrigation system with the adaptation of indigenous knowledge and practices relating to various irrigation management activities such as water allocation, distribution and conflict management. The study is based on structured interview, Focus Group Discussion (FGD) and Key Informant Interview for the data collection. The major battle in FMIS in Nepal that are discussed here are water allocation and distribution, external development, assistance, resource misuse, operation and maintenance, and water tax collection.